Serviços municipais de controle de zoonoses no Estado de São Paulo: diagnóstico situacional - Hardt Gomes, Luciana; Fernandes de Menezes, Ricardo; M. S. de Souza Aranda, Clelia; Vieira, Pedro Antonio (BEPA. Boletim Epidemiológico Paulista, 2011)